Forecasting the effects of radioactive contamination in the event of failure on the radiation dangerous objects - Применко, В.І.; Лук’янчиков, В.А.; Лук’янчиков, А.В. (Proceedings of National Aviation University, 2007)
This article considers developed method of radioactive pollution state modeling in contamination area in case emergency at radioactive dangerous objects and during any term after it.